The Equivalence of Noun Translation in the Movie Subtitle "The Conjuring 2: The Enfield Poltergeist" - Humaira, Megan Asri; Rajagukguk, Zahra Fitrah; Muhdiyati, Iyon; Sya, Mega Febriani; Ariah, Ariah; Rasmitadila,; Aliyyah, Rusi Rusmiati (International Journal of Psychosocial Rehabilitation, 2020)
The role of nouns in a story cannot be underestimated and is very influential. As with a story in a translated text. For this reason, this study was conducted to analyze the equivalence of noun translated that represents participants in a film's subtitle. In conducting research, qualitative methods with content analysis are very appropriate to be used in this study. Which this study also shows that the translation of nouns that are carried out is very concerned about their equivalence so that the meaning to be conveyed by the source language can be well received by the target language, namely in Indonesian.